2020
DOI: 10.3390/pr8091143
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Polymer Grade L-Lactic Acid Production Using Lactobacillus rhamnosus SCJ9 from Low-Grade Cassava Chips by Simultaneous Saccharification and Fermentation

Abstract: The present study aims to examine the process for L-lactic acid production from low-grade cassava chips (LGC) using a two-step fermentation approach (TSF) and simultaneous saccharification and fermentation (SSF) by proficient, newly isolated Lactobacillus rhamnosus strain SCJ9. The optimized medium composition revealed by response surface methodology for TSF was 166 g/L LGC hydrolysate and 20 g/L yeast extract (YE), while other medium components were fixed (g/L) as follows: tween80 (2.0), (NH4)2HPO4 (2.0), CH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…EPSs with a positive charge decreased the Kaolin’s negative electrical charge, leading to flocculates. It was observed that EPSd from the biological soil crust induced the flocculation of fine kaolin particles and enhanced the flocculating process by increasing the concentration of uronic acid in the EPS [ 47 , 48 ]. In addition, the flocculation activity of EPSs is due to their natural anionic charge.…”
Section: Discussionmentioning
confidence: 99%
“…EPSs with a positive charge decreased the Kaolin’s negative electrical charge, leading to flocculates. It was observed that EPSd from the biological soil crust induced the flocculation of fine kaolin particles and enhanced the flocculating process by increasing the concentration of uronic acid in the EPS [ 47 , 48 ]. In addition, the flocculation activity of EPSs is due to their natural anionic charge.…”
Section: Discussionmentioning
confidence: 99%
“…The Plackett-Burman design is a valuable statistical design that is particularly useful when dealing with a large number of potential factors that may influence the targeted product yield. Based on the employment of linear regression analysis, this design helps to identify and prioritize the significant factors affecting the responses of interested products while filtering out irrelevant factors [72]. However, the PBD presents certain limitations.…”
Section: Comparison Of Extracellular β-Glucosidase Production By C Rh...mentioning
confidence: 99%
“…2.6. L-LA Production from Mixed Glucose and Xylose by Coculture Fermentation E. mundtii WX1 was designed for coculture fermentation when combined with Lactobacillus rhamnosus SCJ9, a highly active homofermentative LAB capable of producing L-LA from only glucose [21]. The mixed sugar of glucose and xylose in a ratio of 6:4 was selected as a model for LA fermentation.…”
Section: Identification Of Lab By 16s Rrna Gene Sequence Analysismentioning
confidence: 99%